2010
DOI: 10.1002/bit.22891
|View full text |Cite
|
Sign up to set email alerts
|

Recreating the perivascular niche ex vivo using a microfluidic approach

Abstract: Stem cell niches are composed of numerous microenvironmental features, including soluble and insoluble factors, cues from other cells, and the extracellular matrix (ECM), which collectively serve to maintain stem cell quiescence and promote their ability to support tissue homeostasis. A hallmark of many adult stem cell niches is their proximity to the vasculature in vivo, a feature common to neural stem cells, mesenchymal stem cells (MSCs) from bone marrow and adipose tissue, hematopoietic stem cells, and many… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
95
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(100 citation statements)
references
References 32 publications
3
95
0
Order By: Relevance
“…This is in line with the previous notions that a hallmark of mammalian niches is their proximity to the vascular system [36]. Blood vessels are important not only for oxygenation and nutrition of niche elements but also for providing systemic communications of stem cells.…”
Section: Discussionsupporting
confidence: 91%
“…This is in line with the previous notions that a hallmark of mammalian niches is their proximity to the vascular system [36]. Blood vessels are important not only for oxygenation and nutrition of niche elements but also for providing systemic communications of stem cells.…”
Section: Discussionsupporting
confidence: 91%
“…It has been demonstrated that hemispherical structures with distributions of cells similar to that in the hematon can be made using positive dielectrophoresis [110]. In an attempt to recreate the perivascular niche using a microfluidic approach, Carrion and colleagues [111] suspended endothelial cells within 3D fibrin gels patterned adjacent to stromal cells (either fibroblasts or bone marrow-derived MSCs). They executed a morphogenetic process akin to vasculogenesis, forming a primitive vascular plexus and maturing it into a robust capillary network with hollow, well-defined lumens.…”
Section: Miniaturized 25 -3d-platformsmentioning
confidence: 99%
“…Both MSCs and fibroblasts formed pericytic associations with the ECs but promoted capillary morphogenesis with distinct kinetics. Biochemical assays within the niche revealed that the perivascular association of MSCs required interaction between their α6β1-integrin receptor and EC-deposited laminin [111].…”
Section: Miniaturized 25 -3d-platformsmentioning
confidence: 99%
“…The challenge to create functional artificial tissues is the 3-D patterning of manifold types of cells into a tissue-like structural design. The control of components of 3-D co-culture spatial systems by microfluidics is valuable [342][343][344]. An approach using a hydrogel bi-layer of hepatocytes and endothelial cells has allowed the imitation of interstitial flow for the formation of tissue-like structures by the hepatocytes [345].…”
Section: Tissue Engineering Models On Microfluidic Chipsmentioning
confidence: 99%